Tinjauan Desain Pengembangan E-Modul Interaktif Project Citizen: Inovasi Peningkatan Keterampilan di Era 4.0 - Panut Setiono; Yuli Amaliyah (UNIB Press, 2024)
Learning materials that may bridge the understanding of intelligent and good citizenship in a global context are necessary for the majority of generation Z students enrolled in the University of Bengkulu's Elementary School Pre-Service Teacher Education program. Students who take the Global Perspective course are prepared to be globally aware and ready to adjust to the changing global landscape. The study employs a methodical Dick, Carey & Carey development model, which entails procedures such as learning objective identification, learning analysis, student characteristic analysis, formulation of specific learning objectives, creation of learning materials, learning strategies, assessment instrument development, and formative and summative evaluations. This e-module was designed after a study of the requirements for economic citizenship literacy. Aspects like financial education, social skills, knowledge economy, democratic citizenship, and economic literacy are all included in citizenship literacy. This study finds that Elementary School Pre-Service Teacher Education students at the University of Bengkulu should benefit from improved digital citizenship abilities in the context of the 4.0 era thanks to the interactive e-module Project Citizen. Thus, in addition to enhancing digital literacy, this curriculum also fosters creativity, critical thinking, and other abilities necessary in the digital age.